Kinetic Spectrophotometric Methods for the Determination of Imatinib Mesylate in Pure and Tablet Dosage Form - A. Aly, Fatma; D. Alanazy, Haessah (Asian Journal of Chemistry, 2012)
Simple and sensitive kinetic spectrophotometric methods were established for the determination of imatinib mesylate in pure and in its pharmaceutical dosage forms using alkaline potassium permanganate as an oxidizing agent. The methods involve determination of imatinib mesylate by kinetic studies of its oxidation at room temperature for a fixed time of 5 min. The absorbance of the green coloured manganate ions was measured at 610 nm. Alternatively, the decrease in the absorbance of permanganate upon addition of the studied drug was also measured at 525 nm. The absorbance-concentration plots were rectilinear over the ranges of 1-34 and 2-20 μg/mL for the two methods respectively. The different experimental parameters affecting the reaction were carefully studied and optimized. The stoichiometry of the reaction was determined adopting the limiting logarithmic method. The analytical performance of the proposed methods was fully validated and the results were satisfactory. The proposed methods have a great value in their application to the analysis of imatinib mesylate in quality control laboratories.